Role of macrophage scavenger receptor MSR1 in the progression of non-alcoholic steatohepatitis - Sheng, Wei; Ji, Guang; Zhang, Li (Frontiers in Immunology, 2022)
Nonalcoholic steatohepatitis (NASH) is the progressive form of nonalcoholic fatty liver disease (NAFLD), and the dysregulation of lipid metabolism and oxidative stress are the typical features. Subsequent dyslipidemia and oxygen radical production may render the formation of modified lipids. Macrophage scavenger receptor 1 (MSR1) is responsible for the uptake of modified lipoprotein and is one of the key molecules in atherosclerosis. However, the unrestricted uptake of modified lipoproteins by MSR1 and the formation of cholesterol-rich foamy macrophages also can be observed in NASH patients and mouse models. In this review, we highlight the dysregulation of lipid metabolism and oxidative stress in NASH, the alteration of MSR1 expression in physiological and pathological conditions, the formation of modified lipoproteins, and the role of MSR1 on macrophage foaming and NASH development and progression.